2016
DOI: 10.1016/j.jid.2016.05.105
|View full text |Cite
|
Sign up to set email alerts
|

Natural STING Agonist as an “Ideal” Adjuvant for Cutaneous Vaccination

Abstract: A potent adjuvant without incurring any significant skin reactogenicity is urgently needed for cutaneous vaccination. Here, we report that a natural agonist of STING, 2’3’- cyclic GMP-AMP (cGAMP) robustly augmented and prolonged cellular and humoral immune responses provoked by H5N1 and 2009 H1N1 pandemic influenza vaccines after a single dose of intradermal, but not intramuscular, immunization. The potency of cGAMP for cutaneous vaccination was ascribed to a large number of antigen presenting cells resident i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(100 citation statements)
references
References 33 publications
7
91
1
1
Order By: Relevance
“…The unadjuvanted vaccine was not protective: only 22% of vaccinated animals survived the challenge. ID-delivered cGAMP was previously reported to induce a strong Th-1 response in adult mice via activation of the STING pathway (29,30). However, in our experiments all aged mice immunized ID with the vaccine supplemented with 5 µg cGAMP succumbed to infection upon challenge (Figures 1A,B).…”
Section: Results Cgamp and Quil-a As Individual Adjuvants In Aged Micementioning
confidence: 58%
See 2 more Smart Citations
“…The unadjuvanted vaccine was not protective: only 22% of vaccinated animals survived the challenge. ID-delivered cGAMP was previously reported to induce a strong Th-1 response in adult mice via activation of the STING pathway (29,30). However, in our experiments all aged mice immunized ID with the vaccine supplemented with 5 µg cGAMP succumbed to infection upon challenge (Figures 1A,B).…”
Section: Results Cgamp and Quil-a As Individual Adjuvants In Aged Micementioning
confidence: 58%
“…Saponin was selected because in addition to enhancing membrane permeability for small molecules (51,52) it is an effective adjuvant that stimulates production of proinflammatory cytokines and promotes cellular immune response to protein antigens. Separate studies with cGAMP (30) or Quil-A-containing adjuvants (53) were each reported to stimulate Th1 responses to influenza vaccines in adult mice. The rapid increase in the IgG2a antibody isotype in cGAMP/Quil-A adjuvanted groups that we observed was also consistent with a Th-1 bias of adjuvant action mode (54).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…). Moreover, 2′3′‐cGAMP also acts as an effective adjuvant boosting antigen‐specific T‐cell activation .…”
Section: Identification and Characterization Of The Cgas‐cgamp‐sting mentioning
confidence: 99%
“…In particular, 94 cyclic dinucleotides (CDNs) that activate stimulator of interferon genes (STING, also known 95 as TMEM173, MPYS, ERIS and MITA) and induce a type I interferon (IFN-I) response as 96 well as production of pro-inflammatory cytokines are being developed as adjuvants (Cai et Pyrophosphatase/Phosphodiesterase 1 (ENPP1), an enzyme degrading extracellular ATP and 107 cGAMP (Carozza et al, 2019;Li et al, 2014). Indeed, when injected intra-muscularly, the 108 concentration of cGAMP at the inoculation site decreases rapidly, resulting in a sub-optimal 109 adjuvant effect (Wang et al, 2016). 110…”
Section: Introduction 40mentioning
confidence: 99%